2020
DOI: 10.1158/0008-5472.can-20-1162
|View full text |Cite
|
Sign up to set email alerts
|

A Circle RNA Regulatory Axis Promotes Lung Squamous Metastasis via CDR1-Mediated Regulation of Golgi Trafficking

Abstract: Lung squamous carcinoma (LUSC) is a highly metastatic disease with a poor prognosis. Using an integrated screening approach, we found that miR-671-5p reduces LUSC metastasis by inhibiting a circular RNA (circRNA), CDR1as. Although the putative function of circRNA is through miRNA sponging, we found that miR-671-5p more potently silenced an axis of CDR1as and its antisense transcript, cerebellar degeneration related protein 1 (CDR1). Silencing of CDR1as or CDR1 significantly inhibited LUSC metastases and CDR1 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…Unlike these two kinds of ncRNAs, circRNAs have emerged as more reliable and promising tumor biomarkers owing to their exceptionally stable structure. Advanced genome sequencing techniques have validated the roles of circRNAs in multiple cancers, including hepatocellular carcinoma [29], gastric cancer [30], colorectal cancer [31] and lung squamous cell carcinoma [32]. However, to date, the expression profiles and roles of circRNAs in OS are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike these two kinds of ncRNAs, circRNAs have emerged as more reliable and promising tumor biomarkers owing to their exceptionally stable structure. Advanced genome sequencing techniques have validated the roles of circRNAs in multiple cancers, including hepatocellular carcinoma [29], gastric cancer [30], colorectal cancer [31] and lung squamous cell carcinoma [32]. However, to date, the expression profiles and roles of circRNAs in OS are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike these two kinds of ncRNAs, circRNAs have emerged as more reliable and promising tumor biomarkers owing to their exceptionally stable structure. Advanced genome sequencing techniques have validated the roles of circRNAs in multiple cancer types including hepatocellular carcinoma [24], gastric cancer [25], colorectal cancer [26] and lung squamous carcinoma [27]. However, to date, the expression pro le and role of circRNAs in OS are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study found several miRNAs and mRNAs that may be related to NP through the public datasets, and analyzed the pathways that may participate in the pathological mechanism of NP through GO and KEGG pathway analysis, our research still has some limitations. Circular RNAs (circRNAs) and lncRNAs are non-coding RNA molecules that have recently been reported to regulate the function of miRNAs and affect a variety of complex human diseases (Fan et al 2020 ; Harrison et al 2020 ; Li et al 2020b ). Although there have been some studies on the circRNA regulation in NP (Li et al 2020a ; Wei et al 2020 ; Zhang et al 2020 ), the present public databases still do not include the circRNA expression data of NP.…”
Section: Discussionmentioning
confidence: 99%